Microfluidic Technologies for Miniaturized Analysis Systems - Hardt, Steffen; Schönfeld, Friedhelm (MEMS Reference Shelf,, 2007)
Microfluidic Technologies for Miniaturized Analysis Systems provides a comprehensive overview of the fluidic aspects of Lab-on-a-Chip technology. This book describes the most important and state-of-the-art microfluidic technologies and the underlying principles utilized in the implementation of fluidic protocols of miniaturized analysis systems. This book discusses many of the effects, outcomes, and techniques which are unique to microfluidic systems. The specific components of this technology toolbox are elucidated through research and examples presented by some of the most renowned experts in the field. Microfluidic Technologies for Miniaturized Analysis Systems is an important reference for professionals and academic researchers seeking information about the latest techniques, including: Control and pumping of small amounts of liquid Particle and cell manipulation Micromixing Separation technology Bioanalytic methods About the MEMS Reference Shelf: The MEMS Reference Shelf is a series devoted to Micro-Electro-Mechanical Systems (MEMS), which combine mechanical, optical, or fluidic elements on a common microfabricated substrate to create sensors, actuators, and microsystems. This series strives to provide a framework where basic principles, known methodologies, and new applications are integrated in a coherent and consistent manner. STEPHEN D. SENTURIA, MASSACHUSETTS INSTITUTE OF TECHNOLOGY, PROFESSOR OF ELECTRICAL ENGINEERING, EMERITUS.